2013
DOI: 10.4013/jacr.2013.32.02
|View full text |Cite
|
Sign up to set email alerts
|

A fast feature selection algorithm applied to automatic faults diagnosis of rotating machinery

Abstract: Abstract. This work presents a fast algorithm to reduce the number of features of a classification system increasing the performance without loss of quality. The experiments show that the proposed algorithm can reduce the number of features quickly as well as increase the quality of the predictions simultaneously. Three features extractions were used to generate the initial pool of features of the system. Comparative results of the proposed algorithm with the classical sequential forward selection algorithm ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Feature extraction for vibration analysis has been discussed in numerous publications, extensive reviews can be found for instance in (D. Wang et al, 2017;Singh & Vishwakarma, 2015). The extraction of typical statistical features in time domain is described in (Sharma & Parey, 2016;Lei, He, Zi, & Hu, 2007;Shen, Wang, Kong, & Tse, 2013;Decker & Lewicki, 2003;Alattas & Basaleem, 2007;Boldt, Rauber, & Varejão, 2013;Jalil, Butt, & Malik, 2013;Suma & Gurumurthy, 2010;Kollialil, Gopan, Harsha, & Joseph, 2013). Features in time-frequency and frequency domain are proposed and investigated in (Sharma & Parey, 2016;Lei et al, 2007;Alattas & Basaleem, 2007;Boldt et al, 2013).…”
Section: Methods Lcmmentioning
confidence: 99%
See 1 more Smart Citation
“…Feature extraction for vibration analysis has been discussed in numerous publications, extensive reviews can be found for instance in (D. Wang et al, 2017;Singh & Vishwakarma, 2015). The extraction of typical statistical features in time domain is described in (Sharma & Parey, 2016;Lei, He, Zi, & Hu, 2007;Shen, Wang, Kong, & Tse, 2013;Decker & Lewicki, 2003;Alattas & Basaleem, 2007;Boldt, Rauber, & Varejão, 2013;Jalil, Butt, & Malik, 2013;Suma & Gurumurthy, 2010;Kollialil, Gopan, Harsha, & Joseph, 2013). Features in time-frequency and frequency domain are proposed and investigated in (Sharma & Parey, 2016;Lei et al, 2007;Alattas & Basaleem, 2007;Boldt et al, 2013).…”
Section: Methods Lcmmentioning
confidence: 99%
“…The extraction of typical statistical features in time domain is described in (Sharma & Parey, 2016;Lei, He, Zi, & Hu, 2007;Shen, Wang, Kong, & Tse, 2013;Decker & Lewicki, 2003;Alattas & Basaleem, 2007;Boldt, Rauber, & Varejão, 2013;Jalil, Butt, & Malik, 2013;Suma & Gurumurthy, 2010;Kollialil, Gopan, Harsha, & Joseph, 2013). Features in time-frequency and frequency domain are proposed and investigated in (Sharma & Parey, 2016;Lei et al, 2007;Alattas & Basaleem, 2007;Boldt et al, 2013). Typical symptom parameters in frequency domain for rotating machinery are extracted in (H. Wang & Chen, 2007).…”
Section: Methods Lcmmentioning
confidence: 99%
“…The data are then (1) processed, (2) their features are extracted, and (3) analysis/decisions are performed [1]. Possible features include time-domain features [2,3], but usually frequency domain features are used. Approaches typically use a Fourier transform for feature extraction such as in [4,5], but all these assume a known frequency fingerprint to be extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches typically use a Fourier transform for feature extraction such as in [4,5], but all these assume a known frequency fingerprint to be extracted. In order to specifically construct a feature-space that best suits the application some works define their own feature extraction process [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the fault datasets includes two parts: 480 training samples and 800 testing samples, and each sample includes 52 variables. The further intensive introduction of TE process can be found in the work of Boldt et al [36] The TE process is very close to the actual production process, and it has been extensively applied to evaluate different control and diagnostic strategies in recent years.…”
Section: Introduction Of the Te Processmentioning
confidence: 99%